The Right to Inclusive Education in the Light of the Convention on the Rights of Persons with Disabilities - Diallo, Boubacar Sidi (Wydawnictwo Naukowe UAM, 2018)
This article examines the rights of persons with disabilities in the field of inclusive education based on fundamental human rights outlined in the Convention on the Rights of Persons with Disabilities. Inclusive education is essential to achieve universal respect for the right to education, including persons with disabilities. Only inclusive education systems can offer persons with disabilities both quality education and the opportunity to improve their social situation. Inclusive education is not just about placing students with disabilities in mainstream educational institutions; it also means making them feel welcome, respected and valued. The values that underlie the concept of inclusive education reinforce the capacity of everyone to achieve their goals and to conceive of diversity as a source of enrichment. Students with disabilities need appropriate support to participate in the education system on an equal basis with other students. Ordinary educational institutions must provide students with disabilities with a learning environment that maximizes academic progress and socialization.
Prawo do równego traktowania w edukacji w świetle Konwencji o prawach osób niepełnosprawnych
Keywords: convention; law; education; inclusion; disability; human rights